Modifying wood veneer with silane coupling agent for decorating wood fiber/high-density polyethylene composite. (10th November 2019) - Liu, Yinan; Guo, Limin; Wang, Weihong; Sun, Yanan; Wang, Haigang
Highlight: Two kinds of silane coupling agents (r-aminopropyl triethoxy silane, KH550; and trimethoxy vinyl silane, A171) and dicumyl peroxide were used to bond the wood fiber/high-density polyethylene (WF/HDPE) composite and wood veneer. Samples treated with A171 had higher bonding strength than those treated with KH550. The greater the volume of wood fiber in the WF/HDPE, the poorer the bonding strength of the veneer and the lower its water resistance. Abstract: Because of the smooth, dense, and nonpolar surface of wood-plastic composites (WPCs), it is challenging to form an efficient bonding interface between the WPC and the material of the wood veneer by using traditional adhesives. In this study, two kinds of silane coupling agents (r-aminopropyl triethoxy silane, production number KH550; and trimethoxy vinyl silane, production number A171) and dicumyl peroxide were used to improve the bond between the wood fiber/high-density polyethylene (WF/HDPE) composite and the wood veneer. The attenuated total reflection-Fourier transform infrared spectroscopy curve shows that the two kinds of silane coupling agents were grafted to the surface of the wood veneer, and the contact angle between distilled water and the veneer surface increased from 46° to greater than 120° after treatment. The bonding strength between the treated veneer and the WF/HDPE composite was significantly enhanced, and samples treated with A171 had higher bonding strength than those treated with KH550. The greater the volume of wood fiber in the WF/HDPE, the poorer the bonding strength of the veneer and the lower its water resistance. Images from a scanning electron microscope show that the silane coupling agent A171 can induce a denser interface between the wood veneer and the WF/HDPE composite.